Moving Towards Sustainability: Environmental Management Strategies and Sustainable Infrastructures Development at Universidad Catolica de Córdoba (UCC) - Maria Soledad Perfumo; Leonela Ferraresi; Lelia Imhof (Universitas Diponegoro, 2024)
This study focuses on the